Teacher Evaluation in Mexican Rural Schools: A Political-Educational Analysis - Hernández Herrera, María Teresa (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2020)
In 2013, Mexico reformed the third constitutional article establishing teacher evaluation as one of the key strategies to improve the quality of education. The objective of this article was to analyze the implications of the teacher evaluation reform in rural schools in Mexico through the political-educational concepts of capacity and significant change. For the analysis, a documentary review of the reform to the third constitutional article, official reports on teacher evaluation and academic critiques of it were made. In addition, reference was made to a micro study that presented the experience of a rural school teacher in the state of Aguascalientes, Mexico. The results showed a lack of meaning of the evaluation, qualifying it as decontextualized. In addition, it was shown that the improvement of educational quality is not directly related to the reform of teacher evaluation. Through the case study, the lack of capacity in material and immaterial resources of teachers in rural education was evidenced. Finally, solutions were proposed that seek to contemplate the principle of reciprocity and significant change in Mexican rural schools.